2007
DOI: 10.1093/intimm/dxm022
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive phenotypic analysis of the gut intra-epithelial lymphocyte compartment: perturbations induced by acute reovirus 1/L infection of the gastrointestinal tract

Abstract: Intestinal intra-epithelial lymphocytes (IELs) form a highly specialized lymphoid compartment. IELs consist primarily of T cells that are dispersed as single cells within the epithelial cell layer that surrounds the intestinal lumen. These lymphocytes along with lamina propria lymphocytes are considered to play an important role in the regulation of immune responses. IELs are heterogeneous with regard to phenotype, and they contain sub-populations with diverse functions. In our most recent study, we found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
1
6
0
1
Order By: Relevance
“…RRV infection had no effect on CD8 + TCRγδ IEL, which increased as a proportion of total T cells from 19±4% on day 14 post infection to 47±2% on day 21 and 59±1% on day 35 in both mock- and RRV-infected NOD mice (C. Zufferey and B. S. Coulson, unpublished data). These results confirm previous findings that the TCRγδ IEL frequency in mice reaches ∼50% by 20 days of age, and are consistent with the lack of effect of reovirus infection on TCRγδ IEL frequency compared to control mice [48], [49]. The low level of RRV replication in infant C57BL/6 mice may explain their unaltered numbers of CD8αβ TCRαβ IEL and rapid decrease in PD-L1 expression intestinally.…”
Section: Discussionsupporting
confidence: 91%
“…RRV infection had no effect on CD8 + TCRγδ IEL, which increased as a proportion of total T cells from 19±4% on day 14 post infection to 47±2% on day 21 and 59±1% on day 35 in both mock- and RRV-infected NOD mice (C. Zufferey and B. S. Coulson, unpublished data). These results confirm previous findings that the TCRγδ IEL frequency in mice reaches ∼50% by 20 days of age, and are consistent with the lack of effect of reovirus infection on TCRγδ IEL frequency compared to control mice [48], [49]. The low level of RRV replication in infant C57BL/6 mice may explain their unaltered numbers of CD8αβ TCRαβ IEL and rapid decrease in PD-L1 expression intestinally.…”
Section: Discussionsupporting
confidence: 91%
“…Activated B cells express the GL7 epitope, but mature B cells do not; thus, GL7 serves as a marker for GCs in the immunized spleen and lymph nodes (60,61). Further, our results demonstrating GCT expression in ectopic GCs of the salivary gland and its coexpression on B220 ϩ B cells would suggest that these cells are recently activated MCMV-specific cells, since we have previously found a similar population of B220 ϩ GCT ϩ B cells in PPs after acute stimulation with reovirus (15)(16)(17)(62)(63)(64). In addition, our earlier studies demonstrated that GCT is a marker, which identifies reovirus 1/L-specific precursor and effector CTL in PPs of reovirus 1/Linoculated mice (17,63).…”
Section: Discussionmentioning
confidence: 51%
“…In addition, our earlier studies demonstrated that GCT is a marker, which identifies reovirus 1/L-specific precursor and effector CTL in PPs of reovirus 1/Linoculated mice (17,63). We demonstrated that GCT is expressed by recently activated gut lymphocytes and that this recently stimulated GCT-expressing population preferentially migrated to the intraepithelial compartment and lamina propria following enteric virus infection (16,17). These results suggested that GCT can be used as an activation marker for gut lymphocytes.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…[26][27][28] LPLs constitute the major effector cells along gut mucosal surfaces, whereas IELs are interspersed with enterocytes, thus having direct contact with foreign antigens derived from the gut lumen, and are thought to play a key role in the immune responses toward these antigens and in the pathogenesis of a variety of diseases. 29,30 A role in the repair from experimental colitis in mice has been ascribed to IELs due to the activity of cdT cells, [31][32][33] which represent a major T-cell subpopulation within IELs. 34 While some studies have indicated a regulation of LPLs function by probiotics in IBD, 35 up to now there are no data of a possible involvement of IELs in the protective activity of probiotics in colitis.…”
mentioning
confidence: 99%